Utilização de parâmetros acústicos para quantificação de parâmetros hidrológicos - Emerson de Sousa Costa (2014)
Underwater acoustics in marine environments of great depth has developed enough in communications and defense. Regarding the research related to acoustic propagation in low depth, like rivers for example, this is less developed, especially in Brazil. Due to the great difficulty of observation, because of turbid water in rivers environment, underwater acoustics in shallow water should be seen as an alternative to it can be made from the river bottom evaluation, checking the existence of some other object normal composition of his bed. This paper makes a study of some acoustic propagation model, the simulation model using the method of the normal modes and an experimental setup. Existing acoustic propagation models can be used for shallow water environments and deep waters, observing distinctive characteristics. The results obtained from computer simulation and experiment show good results compared to literature.